Investigating the Information Technology Courses for Pre-service and In-service English Teachers in Hong Kong - Chi Cheung Ruby Yang (Universidad Nacional de Colombia, 2011)
This paper focuses on the views of twenty-six pre-service and eight in-service English teachers in Hong Kong concerning the information technology courses in their teacher education programmes. The findings of the study show that while both software applications and technological integration in teaching are highlighted in the course outline, the instructor focused more on the application aspect, with the technology integration being less emphasised. Another important finding is that PowerPoint was still the most commonly used application in teaching. Likewise, usually the involved pre-service and in-service teachers just simply used different computer applications as alternatives to traditional teaching resources. This may reflect the fact that the information technology courses are not adequate to prepare teachers to teach with it.